1999
DOI: 10.1046/j.1440-1738.1999.00249.x
|View full text |Cite
|
Sign up to set email alerts
|

Geology and thermochronometry of the east edge of the Median Batholith (Median Tectonic Zone): a new perspective on Permian to Cretaceous crustal growth of New Zealand

Abstract: We report new field, petrological and isotopic data and interpretations from one of New Zealand’s major basement geological boundaries, the contact between the east side of the Median Batholith (formerly Median Tectonic Zone) and the allochthonous Mesozoic terranes of the Eastern Province. In the Nelson and Hollyford–Eglinton areas this contact is a Cenozoic fault, the Median Tectonic Line of earlier workers. However, in the Longwood Range, unfaulted pre‐Cenozoic geological relations are preserved intact. Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
123
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(132 citation statements)
references
References 45 publications
7
123
2
Order By: Relevance
“…With re-assembly of the many small continental fragments of the Australian margin (see Gaina et al, 1998a, b;Sutherland, 1999;Hall, 2002) (Fig. 8 (Bishop et al, 1985, Mortimer et al, 1999 (Adams et al, submitted). It may be suggested that, as elsewhere along the former Australian margin, the diachronous eastward propagating development of horst and graben structure provoked the extensive erosion of uplifted basement terranes; whilst subsiding parts were buried and protected from erosion, and thus could not provide detrital zircon to syntectonic basins.…”
Section: A Comparison With New Zealandmentioning
confidence: 99%
“…With re-assembly of the many small continental fragments of the Australian margin (see Gaina et al, 1998a, b;Sutherland, 1999;Hall, 2002) (Fig. 8 (Bishop et al, 1985, Mortimer et al, 1999 (Adams et al, submitted). It may be suggested that, as elsewhere along the former Australian margin, the diachronous eastward propagating development of horst and graben structure provoked the extensive erosion of uplifted basement terranes; whilst subsiding parts were buried and protected from erosion, and thus could not provide detrital zircon to syntectonic basins.…”
Section: A Comparison With New Zealandmentioning
confidence: 99%
“…Elsewhere, the heavily forested and regolith-mantled terrain strongly limits surface observations. Field, petrological, and isotopic data presented by Mortimer et al (1999) refined the geological understanding of the Longwood Range. The eastern side is mostly underlain by the Permian Brook Street Terrane, composed of variably metamorphosed volcanic litharenite, siltstone, breccia, and basaltic lavas.…”
Section: General Geologymentioning
confidence: 98%
“…The central and western parts are underlain by components of the Median Batholith that have intruded the Brook Street Terrane. Mortimer et al (1999) recognised two distinct magmatic suites in the Median Batholith in the region: an eastern suite of isotopically primitive, early Triassic to late Permian gabbroic and trondhjemitic intrusives forming much of the central part of the range, and a more westerly, isotopically less primitive suite of mid Triassic to early Jurassic dioritic to granitic intrusives (Fig. 1).…”
Section: General Geologymentioning
confidence: 99%
See 2 more Smart Citations